Validity of Postmortem Glycated Hemoglobin to Determine Status of Diabetes Mellitus in Corneal Donors. Issue 8 (August 2017) - Soper, Mark C.; Marcovina, Santica M.; Hoover, Caroline K.; Calhoun, Peter M.; McCoy, Kristen E.; Stoeger, Christopher G.; Schmidt, Gregory A.; Arafah, Baha M.; Price, Marianne O.; Szczotka-Flynn, Loretta B.; Lass, Jonathan H.
Abstract : Purpose: To examine the stability of postmortem glycated hemoglobin (HbA1c) measurement and its relationship to premortem glycemia. Methods: Postmortem blood samples were obtained from 32 donors (8 known diabetic) and shipped on ice to a central laboratory to examine the stability of HbA1c measurements during the first 9 postmortem days. Thirty-nine other suspected diabetic donors underwent comparison of premortem and postmortem HbA1c measurements. Results: Postmortem HbA1c measurements remained stable after 9 postmortem days (all measurements within ±0.2% from baseline with a mean difference of 0.02% ± 0.10%). Of the premortem measurements obtained within 90 days before death, 79% were within ±1.0% of the postmortem measurements compared with 40% for measurements more than 90 days apart. Three of the postmortem HbA1c measurements exceeded 6.5% (considered a threshold for diabetes diagnosis), although the medical histories did not indicate any previous diabetes diagnosis. Conclusions: Postmortem HbA1c testing is feasible with current eye bank procedures and is reflective of glycemic control of donors during 90 days before death. HbA1c testing could potentially be a useful adjunct to review of the medical history and records for donor assessment for endothelial keratoplasty suitability and long-term graft success.